Analyst of the Impact of Taxpayer Compliance After Participating in the Tax Amnesty Program in the Food and Beverage Subsector on the Indonesia Stock Exchange - Haryadi, Dedi (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
The purpose of this study was to determine whether there was a significant difference in taxpayer compliance before and after taxpayers participated in the tax amnesty program in food and beverage sub-sector companies on the Indonesia Stock Exchange. Taxpayer compliance in this study was measured by the effective tax rate (ETR), ETR in this study was measured by the authors ETR1 (current tax expense proxy/earnings before tax) and ETR2 (current tax expense/operating cash flow). The population of this study amounted to 60 companies and 19 issuers were obtained as samples of the study using the purposive sampling method with the criteria of issuers having been registered on the IDX in 2016 and issuers participating in the tax amnesty program according to Law No. 11 of 2016. This form of research uses a comparative test. The data analysis technique used a paired data difference test. The results of the study which were processed with the help of SPSS version 25 showed that there was no significant increase in tax compliance as measured by ETR1 and ETR2.